2016
DOI: 10.1063/1.4965087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various cation valence, salinity, pH and temperature on bentonite swelling behaviour

Abstract: Abstract.A major issue for the oil and gas industry is the producing of high water from many fields due to massive water injection. Reducing the water production while improving oil recovery from these fields is a major challenge. Polymer gel has been widely used to shut off water-producing zones, but it is not suitable for high temperature reservoirs (> 100 °C). The aims of the present study were to investigate bentonite particles swelling properties and influence of specific ion type (monovalent/divalent) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The free swelling of bentonite decreased with the increased of cation valence and concentration. The results confirmed that bentonite swelling properties could be controlled and inhibited by varying solution salinities and/or altering interlayer exchangeable cations . The particle size of the commercial API-grade bentonite that is normally utilized as part of drilling mud (<75 μ) is relatively bigger than the previously specified rock matrix diverting agents (<10 μ).…”
Section: Introductionsupporting
confidence: 60%
“…The free swelling of bentonite decreased with the increased of cation valence and concentration. The results confirmed that bentonite swelling properties could be controlled and inhibited by varying solution salinities and/or altering interlayer exchangeable cations . The particle size of the commercial API-grade bentonite that is normally utilized as part of drilling mud (<75 μ) is relatively bigger than the previously specified rock matrix diverting agents (<10 μ).…”
Section: Introductionsupporting
confidence: 60%
“…The experiment was performed using 0.2% wt. NaOH solution to increase the degree of bentonite swelling [39] Temperature and pump 2 pressure during the experiment were 110 °C and 23.6 MPa, respectively. The test results of this experiment are shown in Figure 3.…”
Section: Bentonite Swellingmentioning
confidence: 99%
“…This was due to the fact that the claystone samples were collected directly from the nature without any purification or other processes. Claystone is composed of various minerals, including kaolinite (1), illite (2,11), quartz (3,6,10,12,14,19), vermiculite (5,16), feldspar (7), montmorillonite (8,17), chlorite (9), mica (13), and kaolinite (15,18). In bentonite numerous minerals are found, including illite (2), feldspar (4), quartz (6), and montmorillonite (8,17).…”
Section: Effect Of Swamp Acidic Water On Sample Characterizationmentioning
confidence: 99%
“…The release of Al 3+ owing to fluids with pH of 2-6 was also observed in the study in which it resulted in the development of soil erosion. Meanwhile, Ahmed et al [10] found that the swelling ratio reduced when the pH in soil pores decreased due to acid water. Gratchev and Towhata [11] investigated the potential of changes in the compressibility of marine clay due to soil contamination from the past waste mismanagement.…”
Section: Introductionmentioning
confidence: 99%